Mapping evidence on the impact of junk food on anaemia among adolescent and adult population: a scoping review - Joyce Sangeetha Soans; Judith Angelitta Noronha; Suneel C Mundkur; Baby S. Nayak; Meenakshi Garg; Roshan David Jathanna; Edlin Glane Mathias (BMC Nutrition)
Abstract Background Anaemia is a significant global health issue, with adolescents being a particularly vulnerable group. In developing countries, 27% of adolescents are affected by anaemia, compared to a much lower prevalence of 6% in developed countries. This scoping review aims to investigate the intake of junk food and the development of anaemia, providing a foundation for future research in this field. Methods A systematic search was conducted across Scopus, PubMed, EBSCO, CINHAL, WOS and ProQuest using specific keywords. Inclusion criteria comprised all quantitative studies examining the association between nutrition and the development of anaemia. Articles selected for analysis were restricted to those published in English Language between 2014–2024 and available as full-text articles. Results Among the articles that were screened, 20 articles met the criteria for data extraction. Four studies did not reveal statistically significant correlations between nutrition and the development of anaemia, while two studies provided evidence for significant associations. The findings indicated increased anaemia was associated with (a) fast food intake, western pattern of diet, poor eating habits, omission of breakfast and (b) diminished consumption of fruits and vegetables, iron intake, seafood, nuts, and seeds. Conclusion The existing evidence suggests a link between the consumption of junk food and the prevalence of anaemia among adolescents. However, there is a lack of comprehensive studies that thoroughly explore this connection. This gap in research underscores the urgent need for more in-depth studies to understand how modifiable risk factors like junk food consumption contribute to anaemia in adolescents, with the goal of improving prevention and management strategies. Addressing this issue aligns with Sustainable Development Goal (SDG) 3, which aims to ensure healthy lives and promote well-being for all at all ages, which focuses on ending preventable deaths of children and addressing adolescent health. Additionally, this research also contributes to end hunger, achieve food security, and improve nutrition.